Urban Lives: An Industrial City and Its People During the Twentieth Century - Martin Dribe; Therese Nilsson; Anna Tegunimataka (Oxford University Press, 2024)
Urban Lives emphasizes the importance of a micro-level approach in examining the lives of individuals and families in an industrial city, spanning over a century. The work deepens the understanding of major societal shifts and how they are intertwined with demographic behavior over the past 120 years. These societal transformations encompassed groundbreaking advancements in living standards, a relocation of rural populations to urban hubs, and significant alternations in the fabric of everyday working life, ultimately reshaping people's lives. In conjunction, there were changes in individual life courses, particularly how individuals experienced basic demographic events: births, deaths, marriage, and migration. The volume explores family dynamics, the evolution of health disparities and mortality inequality, the paths of social and economic mobility, and the changing landscapes of immigration and residential segregation. It fills a void in the narrative of twentieth-century demographic, social, and economic history and paints a portrait of how personal choices and behavior were shaped by societal transformation. These shifts, closely linked with industrialization and post-industrialization, coincided with the emergence and culmination of the welfare state. Through the lens of the Swedish industrial city of Landskrona, the volume closes the gap between historical studies and contemporary research, offering original insights into a period seldom explored with a micro-level perspective.
Keywords: 330; industrialization; post-industrialization; demography; mortality; migration; family; socioeconomic status; social class; income; inequality